How Do Halal Component and Marketing Drive Muslim Consumers? - Sari, Mia; Rusydiana, Aam Slamet; Indra, Indra; Avedta, Sherrindra (Journal of Digital Marketing and Halal Industry, 2023)
This research addresses a specific issue within halal marketing, emphasizing its novelty. Despite widespread recognition in marketing literature of the roles played by various halal components and strategies in influencing consumer purchase intentions, there is a distinct research gap in the lack of studies focusing on specific categories. This study aims to fill that gap by examining the relationship between halal awareness, certification, and other marketing elements in shaping the halal purchase intentions of Mixue consumers in Indonesia. Structural equation model analysis of data from 156 Mixue consumers revealed positive correlations between halal awareness, certification, and brand with purchase intentions, while food quality and promotion showed negative and non-significant relationships. Theoretically, the research strives to advance a conceptual model of halal purchase intentions by integrating halal components with marketing elements, contributing to marketing literature with a specific focus on Mixue and its consumers in Indonesia. The practical implications involve a deeper understanding of factors influencing halal product purchase intentions, aiding marketing decision-making and business strategies in this rapidly growing market.